2006
DOI: 10.1051/0004-6361:20065226
|View full text |Cite
|
Sign up to set email alerts
|

Supernova 2006aj and the associated X-Ray Flash 060218

Abstract: Aims. We have studied the afterglow of the gamma-ray burst (GRB) of February 18, 2006. This is a nearby long GRB, with a very low peak energy, and is therefore classified as an X-ray Flash (XRF). XRF 060218 is clearly associated with a supernova -dubbed SN 2006aj. Methods. We present early spectra for SN 2006aj as well as optical lightcurves reaching out to 50 days past explosion. Results. Our optical lightcurves define the rise times, the lightcurve shapes and the absolute magnitudes in the U, V and R bands, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
157
0
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 159 publications
(172 citation statements)
references
References 45 publications
13
157
0
2
Order By: Relevance
“…It was observed by the Chandra satellite on February 26.78 and March 7.55 UT (t 8.8 and 17.4 days) for 20 and 30 ks respectively (Soderberg et al 2006b). The spectroscopic redshift was z = 0.033 (Sollerman et al 2006;Mirabal et al 2006). The corresponding isotropic equivalent energy is E iso = (1.9 ± 0.1) × 10 49 erg (Sakamoto et al 2006) which sets this GRB as having a low luminosity, consistent with most of the GRBs associated with SNe (Liang et al 2006b;Cobb et al 2006;Guetta & Della Valle 2007).…”
Section: Grb 060218 -Sn2006ajmentioning
confidence: 80%
See 2 more Smart Citations
“…It was observed by the Chandra satellite on February 26.78 and March 7.55 UT (t 8.8 and 17.4 days) for 20 and 30 ks respectively (Soderberg et al 2006b). The spectroscopic redshift was z = 0.033 (Sollerman et al 2006;Mirabal et al 2006). The corresponding isotropic equivalent energy is E iso = (1.9 ± 0.1) × 10 49 erg (Sakamoto et al 2006) which sets this GRB as having a low luminosity, consistent with most of the GRBs associated with SNe (Liang et al 2006b;Cobb et al 2006;Guetta & Della Valle 2007).…”
Section: Grb 060218 -Sn2006ajmentioning
confidence: 80%
“…The host galaxy of SN2006aj is a low luminosity, metal-poor star-forming dwarf galaxy (Ferrero et al 2006) with an irregular morphology (Wiersema et al 2007), similar to those of other GRBs associated with SNe (Modjaz et al 2006;Sollerman et al 2006).…”
Section: Grb 060218 -Sn2006ajmentioning
confidence: 96%
See 1 more Smart Citation
“…SN 2006aj, a SN Ic-BL associated with an X-ray flash (e.g., Sollerman et al 2006), also showed a double peak. The early maximum was interpreted as being due to the presence of an extended envelope formed by a dense wind (Campana et al 2006;Waxman et al 2007;Irwin & Chevalier 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The five most solid cases of the SN-GRB connection, with high signal-to-noise and multiple spectra, are usually at low z : SN1998bw/GRB980425 at z = 0.0085 (Galama et al 1998), SN2003dh/GRB030329 at z = 0.1685 (Stanek et al 2003;Hjorth et al 2003;Matheson et al 2003), SN2003lw/GRB031203 at z = 0.10058 (Malesani et al 2004), SN2006aj/GRB060218 at z = 0.0335 (Campana et al 2006;Modjaz et al 2006;Pian et al 2006;Sollerman et al 2006;Mirabal et al 2006;Cobb et al 2006;Kocevski et al 2007), and most recently, SN2010bh/GRB100316D at z = 0.0593 Starling et al 2011), where the SN spectra lines were visible as early as 2 days after the GRB . Two special SNe, SNe 2008D and2009bb, and the potential presence of a jet in them will be discussed below.…”
Section: Solid Cases Of Sn-grb: Sne Ic-bl With Grbsmentioning
confidence: 99%